Iron-manganese composite enzyme-like nanomaterial, preparation method and application thereof
Patent Information
- Application Number
- CN202610833521.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]针对现有技术的不足,本发明旨在提供一种具有pH响应性多酶活性的铁锰复合型类酶纳米材料,以解决现有牙周炎治疗中单一材料抗菌效率低、易产生耐药性及生物安全性差的问题,实现高效的催化杀菌与组织修复
[0026]本发明构建了一种铁锰复合型类酶纳米材料,其在酸性环境中类过氧化物酶活性显著增强,可高效催化产生羟基自由基,对浮游态及生物膜态牙周致病菌均表现出广谱、快速的杀灭作用,抗菌效果优于单一组分纳米材料。动物实验证实,该铁锰复合型类酶纳米材料能有效抑制局部炎症、减少破骨细胞形成、阻断牙槽骨吸收并促进牙周组织重建,疗效优于单一组分,且在有效治疗浓度下表现出良好的生物安全性,为牙周炎治疗提供了一种高效低毒的新型类酶纳米材料策略。
Smart Images

Figure CN122954819A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, specifically to an iron-manganese composite enzyme-like nanomaterial, its preparation method, and its application. Background Technology
[0002] Periodontitis is a chronic inflammatory disease caused by pathogenic bacteria in plaque biofilm and is a leading cause of tooth loss in adults. Current clinical treatment mainly relies on mechanical scaling and antibiotics, but these methods present challenges such as difficulty in deep debridement, the potential to induce bacterial resistance, and postoperative oxidative stress imbalance. Nanozymes are a class of nanomaterials with enzyme-like catalytic activity. Among them, iron(III) oxide (Fe3O4) nanozymes have attracted attention due to their peroxidase (POD)-like activity; however, their catalytic efficiency is significantly affected by the microenvironment, and their antibacterial effect is limited when used alone.
[0003] Current research has explored the use of single Fe3O4 nanoparticles or silver nanoparticles for antibacterial therapy. For example, Fe3O4 nanoparticles are synthesized via co-precipitation, utilizing their POD-like activity to catalyze the generation of hydroxyl radicals (•OH) from H2O2 to kill bacteria. However, the POD catalytic activity of single Fe3O4 nanozymes is low under physiologically neutral conditions and highly dependent on H2O2 concentration, resulting in low bactericidal efficiency in the periodontal microenvironment. Existing technologies lack precise control over the electronic structure of the material surface, making it difficult to achieve synergistic effects of multiple enzyme activities. Summary of the Invention
[0004] (a) Technical problems to be solved
[0005] To address the shortcomings of existing technologies, this invention aims to provide an iron-manganese composite enzyme-like nanomaterial with pH-responsive multi-enzyme activity, in order to solve the problems of low antibacterial efficiency, easy development of drug resistance, and poor biocompatibility of single materials in the current treatment of periodontitis, and to achieve efficient catalytic sterilization and tissue repair.
[0006] (II) Technical Solution
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] In a first aspect, the present invention provides an iron-manganese composite enzyme-like nanomaterial, wherein the enzyme-like nanomaterial is prepared by co-precipitation-hydrothermal method combined with high-temperature calcination of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt and water-soluble transition metal salt in a molar ratio of 1:(0.3~0.7):(0.05~0.3):(0.01~0.1).
[0009] Furthermore, the enzyme-like nanomaterial is composed of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt in a molar ratio of 1:(0.4~0.6):(0.1~0.2):(0.02~0.08).
[0010] Furthermore, the enzyme-like nanomaterial is composed of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt in a molar ratio of 1:0.5:0.075:0.025.
[0011] Furthermore, the trivalent water-soluble iron salt is any one of ferric chloride, ferric sulfate, ferric nitrate, and their hydrates.
[0012] Furthermore, the divalent water-soluble iron salt is any one of ferrous chloride, ferrous sulfate, ferrous nitrate, and their hydrates.
[0013] Furthermore, the water-soluble manganese salt is any one of manganese chloride, magnesium sulfate, manganese nitrate, and their hydrates.
[0014] Furthermore, the water-soluble transition metal salt is any one of the water-soluble gold, silver, copper, cobalt, nickel, titanium, chromium, molybdenum, palladium, and platinum salts.
[0015] Secondly, this invention provides a method for preparing iron-manganese composite enzyme-like nanomaterials, wherein the enzyme-like nanomaterials are prepared according to the following steps:
[0016] Step 1: Dissolve 1-10g of γ-polyglutamic acid in 25-250mL of deionized water to form a viscous solution. Under nitrogen protection, add divalent and trivalent water-soluble iron salts, along with water-soluble manganese salts and water-soluble transition metal salts, and stir until homogeneous.
[0017] Step 2: Under nitrogen protection, add 1.0 mol / L NaOH solution dropwise to adjust the pH to 9.5-10.0. The solution will turn from yellow to black, and Fe3O4 crystal nuclei will be generated. Continue stirring for 30 min.
[0018] Step 3: Transfer the suspension to a high-pressure reactor and react at a constant temperature of 200-220℃ for 24-36 hours to carbonize γ-PGA into a biochar substrate; after the reaction is completed, cool to room temperature, filter, and collect solid product 1.
[0019] Step 4: After washing and drying solid product 1, place it in a tube furnace and calcine it at 500-550℃ under nitrogen protection at a rate of 5-10℃ / min for 3-5 hours. After natural cooling, collect solid product 2.
[0020] Step 5: Disperse solid product 2 with deionized water, perform magnetic separation using a magnet to remove unreacted impurity ions, and vacuum dry to obtain the iron-manganese composite enzyme-like nanomaterial.
[0021] Furthermore, in step (i), the molar ratio of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt is 1:(0.3~0.7):(0.05~0.3):(0.01~0.1).
[0022] Furthermore, in step (i), the molar ratio of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt is 1:(0.4~0.6):(0.1~0.2):(0.02~0.08).
[0023] Furthermore, in step (i), the molar ratio of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt is 1:0.5:0.075:0.025.
[0024] Thirdly, the present invention provides the application of the iron-manganese composite enzyme-like nanomaterials obtained by the above preparation method in the preparation of drugs for treating periodontitis.
[0025] (III) Beneficial Effects
[0026] This invention constructs an iron-manganese composite enzyme-like nanomaterial, which exhibits significantly enhanced peroxidase-like activity in an acidic environment. It can efficiently catalyze the generation of hydroxyl radicals, demonstrating broad-spectrum and rapid killing effects against both planktonic and biofilm-borne periodontal pathogens, with antibacterial efficacy superior to single-component nanomaterials. Animal experiments have confirmed that this iron-manganese composite enzyme-like nanomaterial effectively inhibits local inflammation, reduces osteoclast formation, blocks alveolar bone resorption, and promotes periodontal tissue remodeling, showing superior therapeutic efficacy compared to single-component materials. Furthermore, it exhibits good biocompatibility at effective therapeutic concentrations, providing a novel, highly efficient, and low-toxicity enzyme-like nanomaterial strategy for the treatment of periodontitis. Attached Figure Description
[0027] Figure 1 Morphology and elemental characterization of Mn / Ag-Fe3O4: (A) Transmission electron microscopy (TEM) image of Mn / Ag-Fe3O4; (B) Elemental surface scan (EDX-Mapping) distribution of Mn / Ag-Fe3O4; (C) Energy dispersive X-ray spectrum (EDS) of Mn / Ag-Fe3O4.
[0028] Figure 2Particle size distribution, surface potential and crystal structure analysis of Mn / Ag-Fe3O4: (A) Hydrated particle size distribution of Mn / Ag-Fe3O4 determined by dynamic light scattering method; (B) Zeta potential distribution of Mn / Ag-Fe3O4 in aqueous phase; (C) X-ray diffraction pattern of Mn / Ag-Fe3O4.
[0029] Figure 3 X-ray emission electron spectroscopy of Mn / Ag-Fe3O4.
[0030] Figure 4 Enzyme-like catalytic activity of Mn / Ag-Fe3O4: (A) POD and OXD activity kinetic curves at different pH values; (B) POD and OXD activity kinetic curves at different Mn / Ag-Fe3O4 concentrations; (C) POD and OXD activity kinetic curves of different materials; (D) Comparison of POD and OXD specific activities of Mn / Ag-Fe3O4 and Michaelis-Menten equation; (E) CAT-like activity kinetic curve of Mn / Ag-Fe3O4 and rate comparison with the control group.
[0031] Figure 5 Ion release curve of Mn / Ag-Fe3O4 in PBS.
[0032] Figure 6 Evaluation of the antibacterial activity of Mn / Ag-Fe3O4 against MRSA, E. coli and P. gingivalis: (A) Determination of the minimum inhibitory concentration of Mn / Ag-Fe3O4 against the three bacteria; (B) Time-dependent bactericidal kinetic curves of Mn / Ag-Fe3O4 against the three bacteria; *: P < 0.05, **: P < 0.05, ***: P < 0.01, ****: P < 0.001, ns: P > 0.05.
[0033] Figure 7 Evaluation of the antibacterial activity of Mn / Ag-Fe3O4 against MRSA, E. coli and P. gingivalis: (A) Plate colony growth and colony count bar chart of the three bacteria after treatment with Mn / Ag-Fe3O4 nanozyme; *: P < 0.05, **: P < 0.05, ***: P < 0.01, ****: P < 0.001, ns: P > 0.05.
[0034] Figure 8 Quantitative analysis of the inhibitory effect of Mn / Ag-Fe3O4 on bacterial biofilm biomass using crystal violet staining method; *: P < 0.05, ns: P > 0.05.
[0035] Figure 9Inhibitory effect of Mn / Ag-Fe3O4 on biofilms of MRSA, E. coli and P. gingivalis; (A) Crystal violet staining results of bacterial biofilms treated with Mn / Ag-Fe3O4; (B) Distribution of live and dead bacteria in bacterial biofilms before and after Mn / Ag-Fe3O4 treatment observed by laser confocal microscopy.
[0036] Figure 10 Three-dimensional images of alveolar bone in rats with periodontitis after Mn / Ag-Fe3O4 treatment: (A) Sagittal Micro-CT images showing the alveolar bone defect morphology in the maxillary second molar region of rats after treatment in each group; (B) Quantitative analysis of bone metrology parameters: (i) amount of alveolar bone loss, (ii) bone volume fraction, (iii) trabecular bone thickness, (iv) trabecular bone separation; *: P < 0.05, **: P < 0.05, ***: P < 0.01, ****: P < 0.001, ns: P > 0.05.
[0037] Figure 11 Pathological analysis of periodontal tissues after treatment with Mn / Ag-Fe3O4, Ag NPs, and Fe3O4 NPs: (A) H&E staining images of periodontal tissues in the maxillary molar region of rats in each group; (B) Masson trichrome staining images of periodontal tissues in the maxillary molar region of rats in each group.
[0038] Figure 12 Histopathological evaluation of major organs in rats after local treatment with Mn / Ag-Fe3O4. Detailed Implementation
[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Example 1
[0041] Preparation and characterization of iron-manganese composite enzyme-like nanomaterials (Mn / Ag-Fe3O4)
[0042] 1. Preparation of Mn / Ag-Fe3O4
[0043] (1) Preparation of the precursor mixture: 2 g of γ-polyglutamic acid (γ-PGA) was dissolved in 50 mL of deionized water and stirred until completely dissolved to form a viscous solution. FeCl2·4H2O (0.01 mol), FeCl3·6H2O (0.02 mol), MnCl2·4H2O (0.0015 mol), and AgNO3 (0.0005 mol) were added sequentially to uniformly disperse the metal ions in the γ-PGA solution. The entire process was carried out under a nitrogen atmosphere to prevent Fe... 2+ Oxidation. (2) Coprecipitation reaction: Under nitrogen protection, 1.0 mol / L NaOH solution was added dropwise to the above mixed solution to adjust the pH to 10.0; as the alkali solution was added, the solution gradually turned black, indicating that Fe 3 + / Fe 2+ Fe3O4 crystal nuclei were co-precipitated, and stirring was continued for 30 min to ensure complete precipitation.
[0044] (3) Hydrothermal treatment: The above suspension was transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner, sealed and placed in an oven, and reacted at a constant temperature of 200℃ for 24 h. During this process, γ-PGA underwent hydrothermal carbonization to form a biochar substrate, and Fe3O4 nanoparticles and their doped components grew in situ on the carbon surface and were stably attached.
[0045] (4) High-temperature calcination: The product after hydrothermal reaction was naturally cooled to room temperature, washed three times each with ethanol and deionized water, centrifuged, and then dried in a vacuum drying oven at 60℃ for 12 h. Then the dried solid powder was placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min under nitrogen protection, and calcined for 3 h to further carbonize the biochar and improve the crystallinity of the composite material;
[0046] (5) Product purification: The calcined product was dispersed in deionized water, and the magnetic composite material was separated using a strong magnet. The supernatant was discarded, and the process was repeated several times to remove unreacted ions and non-magnetic impurities. The final product was dried under vacuum at 60°C and then stored to obtain Mn / Ag-Fe3O4 enzyme nanomaterials.
[0047] Furthermore, ferric chloride and its hydrate can be replaced with any one of ferric sulfate, ferric nitrate and its hydrate.
[0048] Furthermore, ferrous chloride and its hydrate can be replaced with any one of ferrous sulfate, ferrous nitrate and its hydrate.
[0049] Furthermore, manganese chloride and its hydrate can be replaced with any one of magnesium sulfate, manganese nitrate and its hydrate.
[0050] Furthermore, silver nitrate can be replaced with any one of the water-soluble salts of gold, copper, cobalt, nickel, titanium, chromium, molybdenum, argon, or platinum.
[0051] 2. Characterization of Mn / Ag-Fe3O4
[0052] Transmission electron microscopy (TEM) revealed that the Mn / Ag-Fe3O4 nanoparticles exhibited a relatively uniform size distribution with an average particle size of 10 nm (A). Clear lattice fringes were observed in the high-resolution TEM image, and the coexistence of Fe3O4 and Ag nanoparticles was confirmed by measuring the interplanar spacing and comparing it with a standard card. Elemental surface scanning (EDX mapping) clearly showed the distribution of five elements—Fe, Mn, Ag, O, and C—in the selected region (B). The Fe and O signals highly overlapped, consistent with the Fe3O4 structure; Ag was distributed as dispersed dot-like signals, indicating that silver exists in nanoparticle form without significant agglomeration; while the Mn signal was uniformly dispersed throughout the region, preliminarily confirming that Mn had been successfully doped into the Fe3O4 lattice. Figure 1 C).
[0053] Dynamic light scattering (DLS) test results ( Figure 2 A) indicates that the hydration kinetics particle size distribution of Mn / Ag-Fe3O4 in the aqueous phase is mainly concentrated in the range of 768.5–1039 nm, with a peak at 893.8 nm and an average particle size of approximately 1000 nm.
[0054] The Zeta potential test results (B) show that the peak Zeta potential of Mn / Ag-Fe3O4 appears around -14.91 mV, indicating that its surface carries a negative charge. This negative charge may originate from the functional groups such as carboxyl groups modified on the material surface, which help prevent particle aggregation through electrostatic repulsion and may affect its interaction with bacterial cell membranes.
[0055] The X-ray diffraction (XRD) pattern is shown in Figure C. The distinct diffraction peaks at 2θ = 30.1°, 35.5°, 43.1°, 53.4°, 57.0°, and 62.6° correspond to the (220), (311), (400), (422), (511), and (440) crystal planes of Fe3O4 (JCPDS No. 19-0629), respectively, confirming the successful synthesis of the spinel structure. The weak 2θ diffraction peaks at 38.1° and 44.3° correspond to the (111) and (200) crystal planes of metallic silver, respectively, indicating the presence of elemental silver nanoparticles in the sample. Furthermore, the absence of obvious independent manganese oxide characteristic peaks in the spectrum, combined with subsequent elemental distribution analysis results, suggests that Mn may have been successfully doped into the Fe3O4 lattice in ionic form, leading to a slight broadening and shift of the Fe3O4 characteristic peaks.
[0056] The X-ray photoelectron spectroscopy (XPS) full spectrum (3) confirmed the presence of five elements: Fe, Mn, Ag, O, and C. Peak fitting was performed on the high-resolution spectrum of Fe 2p, revealing two main peaks at binding energies of 710.9 eV and 724.5 eV, corresponding to Fe 2p... 3 / 2 and Fe 2p 1 / 2 Orbit, which conforms to Fe 3+ Typical characteristics. Satellite peak characteristics indicate that Fe mainly exists as Fe. 3 + It exists in the form of a small amount of Fe. 2+ The Mn 2p spectrum shows peaks around 642.1 eV and 653.8 eV, corresponding to Mn 2p peaks, respectively. 3 / 2 and Mn 2p 1 / 2 This indicates that the manganese in the material is Mn. 2+ and Mn 3+ The presence of mixed valence states often contributes to improved catalytic performance of materials. Ag 3d spectra show that Ag 3d... 5 / 2 and Ag 3d 3 / 2 The binding energies are located at 368.0 eV and 374.0 eV, respectively, which are consistent with the standard values for elemental silver, indicating that silver exists in a metallic state. Fitting the O 1s spectrum reveals three peaks, representing oxygen in the crystal lattice, hydroxyl groups on the material surface, and adsorbed water molecules, respectively. The abundance of surface hydroxyl groups demonstrates that these groups act as active sites, participating in and catalyzing the reaction and promoting its progress.
[0057] Detection of three types of peroxidase and oxidase-like activities
[0058] 3.1 Experimental Methods
[0059] (1) Detection of peroxidase (POD) activity
[0060] The POD activity of Mn / Ag-Fe3O4 was quantitatively determined using 3,3',5,5'-tetramethylbenzidine (TMB) as a chromogenic substrate in an acetate-sodium acetate buffer system at pH 4.5.
[0061] ①Reagents: Acetic acid-sodium acetate buffer solution (0.2 M, pH 4.5); H2O2 solution (30%, diluted to the required concentration before use); TMB stock solution (20 mg / mL, prepared by dissolving in DMSO, stored at -20℃ protected from light).
[0062] ② Reaction system: In a 96-well plate, add 84 µL of buffer, 10 µL of enzyme-like nanomaterial sample dispersion (final concentration adjusted according to the experimental design), 5 µL of H2O2 solution (final concentration 5 mM), and finally add 1 µL of TMB stock solution (final concentration 0.83 mM) to start the reaction. The total system volume is 100 µL. Set up wells without nanozymes or H2O2 as controls.
[0063] ③ Detection: Immediately place the 96-well plate in a multi-functional microplate reader preheated to 37°C, and continuously monitor the absorbance change at a wavelength of 652 nm at 30-second intervals for 5 minutes.
[0064] ④ Enzyme activity calculation: Select the absorbance change rate (ΔA / Δt) during the initial linear phase of the reaction, and substitute it into the formula to calculate the enzyme activity: U = V × (ΔA / Δt) / (ε × l)
[0065] Where U represents enzyme activity; V represents the reaction volume (0.1 mL); and ε is the molar extinction coefficient of TMB at 652 nm (39000 M). -1 ·cm -1 ); l is the optical path length of the liquid layer in the 96-well plate (0.3 cm). Specific activity (U / mg) is the ratio of enzyme activity to the mass of the added enzyme-like nanomaterial.
[0066] (2) Detection of oxidase-like (OXD) activity
[0067] The OXD activity of Mn / Ag-Fe3O4 in direct catalytic substrate oxidation was evaluated under conditions without exogenous H2O2.
[0068] ① Reagents: Acetic acid-sodium acetate buffer solution (0.2 M, pH=4.5); TMB stock solution.
[0069] ② Reaction system construction: 89 µL of buffer solution, 10 µL of enzyme-like nanomaterial sample dispersion, and finally 1 µL of TMB stock solution (final concentration 0.83 mM) were added sequentially to a 96-well plate to start the reaction, with a total reaction volume of 100 µL. Wells without enzyme-like nanomaterials were also included as controls.
[0070] ③ Detection and calculation: The detection steps and enzyme activity calculation methods are the same as those for POD activity detection.
[0071] 3.2 Experimental Results
[0072] Experimental results show that Mn / Ag-Fe3O4 exhibits multi-enzyme activities, including oxidase-like (OXD), peroxidase-like (POD), and catalase-like (CAT) activities. In an acidic buffer containing H2O2 (pH 4.5), this enzyme nanomaterial efficiently catalyzes the oxidation of TMB, with its absorbance at 652 nm increasing rapidly over time. Based on the POD activity kinetics data of Mn / Ag-Fe3O4 at pH 4.5 and a concentration of 100 µg / mL, the initial reaction rate was calculated to be 0.18 ΔA / min. Even without exogenous H2O2, this enzyme nanomaterial can still directly catalyze the oxidation of TMB by dissolved oxygen, exhibiting intrinsic OXD activity. Under the same conditions, its OXD reaction rate is 0.16 ΔA / min (A).
[0073] The catalytic activity of Mn / Ag-Fe3O4 is affected by both the pH of the surrounding environment and its own concentration. POD activity increases significantly with increasing concentration, with the reaction rate at 100 µg / mL being four times higher than at 25 µg / mL (B). Both POD and OXD activities of Mn / Ag-Fe3O4 are stronger under acidic conditions, exhibiting optimal activity in the pH range of 4.5–5.0. This is consistent with typical Fenton-like reactions and simulated acidic inflammatory microenvironments.
[0074] Compared with single-component Fe3O4 nanoparticles or Ag nanoparticles, the POD activity of Mn / Ag-Fe3O4 enzyme nanomaterials was significantly improved, indicating that the synergistic doping of Mn and Ag effectively enhanced its catalytic performance. Furthermore, control experiments showed that Fe3O4 nanoparticles alone exhibited only weak catalytic activity, while Ag nanoparticles alone did not show significant POD or OXD activity under the test conditions (C). Further enzyme kinetic analysis revealed the POD and OXD specific activities and Michaelis constants of the Mn / Ag-Fe3O4 enzyme nanomaterials as shown in Figure D.
[0075] In addition to POD and OXD activities, Mn / Ag-Fe3O4 also exhibited detectable catalase-like activity in a neutral environment. Dissolved oxygen meter monitoring data (E) showed that the initial oxygen production rate of H2O2 decomposition catalyzed by Mn / Ag-Fe3O4 (50 µg / mL) was 0.52 ± 0.03 mg / (L·min), which was 5 times the spontaneous decomposition rate of H2O2 (0.10 ± 0.02 mg / (L·min). In the periodontal microenvironment, the CAT activity and pH-responsive POD activity of Mn / Ag-Fe3O4 were enhanced.
[0076] 4. Analysis of Mn / Ag-Fe3O4 ion release behavior
[0077] The ion release of Mn / Ag-Fe3O4 after incubation in PBS buffer (pH 7.4) at 37°C for different times was determined by inductively coupled plasma mass spectrometry (ICP-MS). Figure 5 The results showed that Fe, Mn, and Ag all exhibited significant release behavior, and the release amount increased with time.
[0078] After 3 hours of incubation, the release concentrations of the three ions were as follows: Ag + (5.18±0.18 µg / mL) > Fe ions (4.30±0.68 µg / mL) > Mn ions (1.42±0.08 µg / mL). After 24 h, ion release further increased, Ag ions... + Ag+ ions (29.85±0.48 µg / mL) > Fe ions (5.00±0.59 µg / mL) > Mn ions (1.94±0.04 µg / mL). The Ag+ release concentration was highest at 24 h, 5.8 times that of the initial 3 h, indicating a continuous and significant release process. The release of Fe and Mn ions was relatively gradual, increasing by only 16% and 37% respectively within 24 h. This slow and continuous ion release behavior suggests that Mn / Ag-Fe3O4 is relatively stable in the physiological environment, but can still release ions (especially Ag+) through controlled release. + Ag provides potential long-term antibacterial effects. + The release may originate from the slow oxidative dissolution of Ag nanoparticles on the material surface, which corresponds to the trace amounts of Ag detected in XPS analysis. + The signals match.
[0079] Example 2
[0080] In vitro antibacterial test of Mn / Ag-Fe3O4
[0081] 1 Experimental Methods
[0082] 1.1 Experimental bacterial strains
[0083] Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli (E. coli), and Porphyromonas gingivalis (P. gingivalis) were selected as research subjects to explore the in vitro antibacterial potential of Mn / Ag-Fe3O4. The three bacterial strains were activated and cultured to the logarithmic growth phase using standard methods for later use. MRSA and E. coli were cultured on LB medium, and P. gingivalis was cultured on BHI medium.
[0084] 1.2 Experimental Grouping
[0085] ① Blank control group: bacteria + sterile PBS
[0086] ② Concentration gradient group: bacteria + Mn / Ag-Fe3O4 dispersions of different concentrations, namely 12.5, 25, 50, 100, and 200 µg / mL.
[0087] ③ Material control group: bacteria + dispersions of different materials, namely silver nanoparticles (Ag NPs), iron oxide nanoparticles (Fe3O4 NPs), and Mn / Ag-Fe3O4.
[0088] ④ Negative control group: Contains only sterile PBS or culture medium, used to verify the sterility of the experimental system.
[0089] Each group should have at least 3 replicates, and all experiments should be repeated 3 times independently.
[0090] 1.3 Determination of Minimum Inhibitory Concentration (MIC)
[0091] In a 96-well plate, add bacterial suspension diluted with fresh culture medium to each well, and serially dilute the Mn / Ag-Fe3O4 dispersion with the same culture medium to adjust the final bacterial concentration in each well to 2 × 10⁻⁶. 5 The final concentrations of CFU / mL and Mn / Ag-Fe3O4 were set at 200, 100, 50, 25, and 12.5 µg / mL, respectively, with a total liquid volume of 200 µL per well. Negative control wells with only culture medium and positive control wells with only bacteria and culture medium were also included. Each nanozyme concentration was replicated in triplicate.
[0092] Under appropriate conditions, 96-well plates were cultured: aerobic bacteria were cultured at 37°C for 3 h, and *Porphyromonas gingivalis* was cultured in an anaerobic environment at 37°C for 24 h. After the experiment, the 96-well plates were placed in a microplate reader, and the absorbance (OD) of the solution in each well was measured at a specific wavelength of 600 nm.600 Using the positive control group as a reference, the control group was selected based on its ability to inhibit bacterial growth, meaning that no obvious turbidity was observed in the wells and the OD value was [not specified]. 600 The lowest nanozyme concentration that is equivalent to that of the negative control group is determined as its minimum inhibitory concentration (MIC).
[0093] 1.4 Time-based sterilization curve
[0094] Dilute the bacterial culture that has reached the logarithmic growth phase with fresh culture medium to a concentration of 1×10⁻⁶ per milliliter. 6 The bacteria were divided into two experimental groups: ① blank control group (bacterial suspension only) and ② material treatment group (bacterial suspension mixed with different concentrations of Mn / Ag-Fe3O4 nanozyme). Each group was placed under suitable shaking culture conditions, and the OD value at 600 nm was measured at 0, 1, 2, 4, 6, 8 and 24 h, respectively, and time sterilization curves were plotted.
[0095] 1.5 Colony forming unit count
[0096] In sterile centrifuge tubes, the bacterial suspensions in the logarithmic growth phase were diluted to the predetermined concentrations using their respective fresh culture media (MRSA and E. coli were diluted with LB medium, and P. gingivalis were diluted with BHI medium). The drug solution or control solution was then added and mixed to 1 mL, ensuring a final bacterial concentration of 1 × 10⁻⁶. 6 CFU / mL. After gently mixing by pipetting, the settings for each group are as follows:
[0097] Blank control group: bacterial culture + equal volume of sterile PBS.
[0098] Different material groups: bacterial culture + equal volumes of nano-Ag (Ag NPs), nano-Fe3O4 (Fe3O4 NPs), and Mn / Ag-Fe3O4 dispersion, all with a final concentration of 100 µg / mL. (Ag NPs and Fe3O4 NPs were commercially available products purchased from Shanghai Maclean Biochemical Technology Co., Ltd.)
[0099] MRSA and E. coli: cultured at 37℃ on a shaker at 180 rpm for 3 h; P. gingivalis: cultured anaerobically at 37℃ for 24 h.
[0100] After incubation, the bacterial suspensions from each group were vortexed. After serial dilution with sterile PBS, the solutions were plated onto their respective solid culture media: MRSA and E. coli were plated on LB agar plates and incubated at 37°C for 24 h; P. gingivalis were plated on BHI blood agar plates and incubated in an anaerobic environment at 37°C for 5–7 days. After incubation, plates with clear and evenly distributed colonies were selected for counting; a colony count between 30 and 300 was ideal. The entire experiment was repeated three times.
[0101] 1.6 Inhibitory effect of Mn / Ag-Fe3O4 on biofilm
[0102] 1.6.1 Quantitative analysis of crystal violet staining for biological membranes
[0103] (1) Biomembrane construction
[0104] Take fresh culture medium and measure the OD of the bacterial suspension in the logarithmic growth phase. 600 Adjust the pH to 0.2 and add 200 µL to each well of a 96-well plate. Incubate MRSA and E. coli at 37°C for 24 h; incubate P. gingivalis under anaerobic conditions at 37°C for 24 h. After incubation, gently wash twice with PBS to remove bacteria attached to the surface. Set up three replicates for each drug concentration.
[0105] (2) Drug treatment
[0106] Control group: biofilm + 180µL culture medium + 20µL PBS
[0107] Materials group: biofilm + 180µL culture medium + 20µL 1mg / mL Ag NPs, Fe3O4 NPs and Mn / Ag-Fe3O4, so that the final concentration of each is 100µg / mL.
[0108] Culture conditions: MRSA and E. coli were cultured in a constant temperature incubator at 37℃ for 3 h; P. gingivalis were incubated in an anaerobic environment at 37℃ for 24 h.
[0109] (3) Staining and quantification
[0110] Discard the liquid in the wells, add 200 µL of 4% paraformaldehyde to each well, and fix at room temperature for 15 min. Wash three times with PBS, air dry, add 100 µL of 0.1% crystal violet, cover and protect from light, and stain for 30 min. Then rinse thoroughly with deionized water, air dry, add 200 µL of 96% ethanol to each well, and react in the dark for 1 h. Finally, aspirate 100 µL of supernatant to a new 96-well plate and read the values using a microplate reader.
[0111] (4) Results processing
[0112] Biofilm inhibition rate (%) = (OD value of control group - OD value of experimental group) ÷ OD value of control group × 100%. Results are expressed as mean ± standard deviation.
[0113] 1.6.2 Confocal microscopy observation of live and dead bacteria stained in biofilms
[0114] (1) Preparation of biofilm samples
[0115] Following the method in 1.6.1, a biofilm was constructed in a chamber culture dish.
[0116] (2) Nanoenzyme material treatment
[0117] Control group: biofilm + 180 µL fresh culture medium + 20 µL sterile PBS
[0118] Materials Experiment Group: Biomembrane + 180 µL fresh culture medium + 20 µL dispersions of different nanomaterials (final concentration 100 µg / mL): Ag NPs group, Fe3O4 NPs group, Mn / Ag-Fe3O4 group
[0119] MRSA was cultured with E. coli at 37℃ for 3 h, and P. gingivalis was cultured anaerobically at 37℃ for 24 h.
[0120] (3) Staining of live and dead bacteria
[0121] Following the instructions of the live / dead bacteria activity assay kit, dilute SYTO 9 and propidium iodide (PI) to working concentrations (2.5 µM each) with sterile PBS. After treatment, aspirate the culture medium, carefully wash the biofilm twice with PBS, and add 200 µL of pre-mixed SYTO 9 / PI staining working solution (1:1 volume ratio) to each well, ensuring complete coverage of the biofilm. Incubate at room temperature in the dark for 15 min. Carefully aspirate the staining solution, and gently wash once with PBS to remove any unstained excess dye.
[0122] (4) Observation by confocal microscope
[0123] When live bacteria are labeled with SYTO 9 dye, they fluoresce green under a confocal microscope; while dead bacteria, stained with propidium iodide (PI), fluoresce red under a confocal microscope. During observation, oil immersion lenses of different magnifications were used to perform Z-axis layered scanning of the biofilm, acquiring images at 1µm intervals from top to bottom. Three different regions were randomly selected from each sample well for imaging. All acquired raw images were saved as a 3D data stack for subsequent 3D reconstruction and quantitative analysis.
[0124] (5) Image analysis
[0125] ImageJ software was used for image processing and analysis to calculate the ratio of live to dead bacteria.
[0126] 1.7 Statistical Analysis
[0127] All experiments were independently repeated three times, and results are expressed as mean ± standard deviation. Statistical analysis was performed using SPSS software. One-way ANOVA was used for comparisons among multiple groups; if differences were statistically significant, pairwise comparisons were further performed using the LSD method. P < 0.05 was considered statistically significant.
[0128] 2 Results
[0129] 2.1 Minimum Inhibitory Concentration and Bactericidal Kinetics
[0130] The results of the minimum inhibitory concentration determination are shown in the figure. Figure 6 A shows that Mn / Ag-Fe3O4 has significant antibacterial activity against all three tested pathogenic bacteria, with a MIC value of 100 µg / mL for each.
[0131] The time-based sterilization curve (B) shows that:
[0132] ① For MRSA: Bacterial growth was significantly inhibited at a concentration of 100 µg / mL Mn / Ag-Fe3O4. After 4 h of treatment, the absorbance of the experimental group was 1% of that of the control group. After 24 h of treatment, bacterial growth was still effectively inhibited, with an average OD of 0.39, while the bacteria in the untreated group had entered the stationary phase, with an average OD of 0.60.
[0133] ② For E. coli: At a concentration of 100 µg / mL, Mn / Ag-Fe3O4 showed a more thorough bactericidal effect. After 4 h of treatment, the average OD value was close to the baseline at 0.019, significantly lower than the average OD value of 0.267 in the control group. After 24 h of treatment, the average OD value of the experimental group dropped to a negative value of -0.061, indicating that lysis had occurred.
[0134] ③ For P. gingivalis: At a concentration of 100 µg / mL, Mn / Ag-Fe3O4 showed bactericidal activity in the early stages of treatment (2 h to 4 h) (the average OD value dropped to a negative value). Although some bacterial resuscitation occurred between 8 h and 24 h, the final average OD value of 0.30 after 24 h was still significantly lower than the average OD value of 0.37 in the control group, indicating that it has sustained antibacterial ability.
[0135] The time-killing curves confirmed that Mn / Ag-Fe3O4 has rapid and efficient antibacterial activity against Gram-positive bacteria (MRSA), Gram-negative bacteria (E. coli), and anaerobic bacteria (P. gingivalis) at a concentration of 100 µg / mL.
[0136] 2.2 Colony Count
[0137] After treatment with 100 µg / mL Mn / Ag-Fe3O4 nanozyme for 3 h of aerobic bacteria and 24 h of anaerobic bacteria, the viable counts of MRSA and P. gingivalis decreased by 5 log units compared to the PBS control group, and E. coli decreased by 4 log units. In contrast, the same concentrations of single-component Ag NPs and Fe3O4 NPs showed only weak antibacterial effects against the three bacteria (a decrease in viable count of 0.5–1.5 log units), far less effective than the bactericidal effect of Mn / Ag-Fe3O4. Figure 7 ).
[0138] 2.3 Inhibitory effect on biomembranes
[0139] 2.3.1 Quantitative analysis of biofilm biofilms
[0140] The quantitative results of crystal violet staining are shown in the figure. 100 µg / mL Mn / Ag-Fe3O4 effectively inhibited and removed pre-formed mature biofilms. Compared with the control group without added material, the groups treated with Mn / Ag-Fe3O4 showed a significant reduction in biofilm formation. The inhibition rate was 28.2% for MRSA biofilm, 48.1% for E. coli biofilm, and 52.1% for P. gingivalis biofilm. The biofilm inhibition effect of Mn / Ag-Fe3O4 was significantly better than that of single-component materials at the same concentration. Under the same conditions, the inhibition rates of nano-Ag and nano-Fe3O4 on the three types of biofilms were generally low, only one-third to one-half that of Mn / Ag-Fe3O4. These results indicate that Mn / Ag-Fe3O4 can effectively disrupt pre-formed bacterial biofilms, especially showing a more pronounced effect on the removal of P. gingivalis and E. coli biofilms (inhibition rate >48%). Its effect is significantly better than that of single Ag or Fe3O4 nanoparticles.
[0141] 2.3.2 Distribution of live and dead bacteria within the biofilm
[0142] Figure 9 A represents the results of live and dead bacterial staining under a laser confocal microscope, such as... Figure 9 As shown in Figure A, the biofilm structure of the PBS control group was intact and dense, dominated by green fluorescent live bacteria, accounting for 84.8%. After treatment with Mn / Ag-Fe3O4, the biofilm structure was significantly disrupted, and the red fluorescent dead bacteria signal was enhanced in three-dimensional space, indicating that this type of enzyme-based bactericidal material can effectively penetrate and kill bacteria inside the biofilm.
[0143] from Figure 9B shows that the proportion of viable bacteria in the biofilm of the Mn / Ag-Fe3O4 treated group decreased significantly to 36.3%, corresponding to a dead bacteria proportion of 63.7%, demonstrating a significant antibacterial effect. In contrast, the effects of single-component materials at the same concentration were limited: the viable bacteria proportion in the nano-Ag group was 78.5%, and in the nano-Fe3O4 group it was 79.3%, with only a slight increase in the dead bacteria proportions compared to the control group. CLSM imaging and quantitative analysis jointly confirmed that Mn / Ag-Fe3O4 not only disrupts the biofilm structure but also effectively kills bacteria embedded deep within the biofilm, with a significantly higher bactericidal efficiency than single Ag NPs or Fe3O4 NPs. This indicates that Mn / Ag-Fe3O4 enhances its ability to remove bacteria from biofilms through a synergistic effect.
[0144] Example 3
[0145] Therapeutic effect of Mn / Ag-Fe3O4 on a rat model of periodontitis
[0146] 1 Method
[0147] 1.1 Model Establishment
[0148] ① Periodontal ligation modeling: Experimental rats were fasted for 12 hours before surgery and anesthetized by intraperitoneal injection of 2% sodium pentobarbital solution at a dose of 40 mg / kg body weight. After anesthesia, the rats were properly fixed on the operating table, and their maxillary second molars were fully exposed. Subsequently, a 0.2 mm diameter stainless steel orthodontic ligation wire was used to circumferentially ligate the cervical region of the molar, and the ligation wire was gently pressed into the gingival sulcus around the tooth to ensure firm fixation. This was continued for 4 weeks to establish an experimental periodontitis model.
[0149] ② Bacterial inoculation: Collect *P. gingivalis* cells by centrifugation and resuspend in pre-reduced BHI medium containing 2% sodium carboxymethyl cellulose to a final volume of 1 × 10⁻⁶. 9 CFU / mL. Starting from the first day after ligation, 0.1 mL of bacterial solution was slowly inoculated into the gingival sulcus of each ligated tooth and around the ligation line using a microsyringe under mild ether anesthesia for 4 consecutive weeks.
[0150] ③ Model maintenance: The ligature wire is retained until the 4th week, during which time it is checked and tightened weekly to prevent loosening.
[0151] Four weeks after ligation, periodontal clinical indicators (PD, BI, TM) were measured in all rats under anesthesia. Rats were then sacrificed under over-anesthesia, and maxillary bone tissue was dissected and fixed overnight in 4% paraformaldehyde. Alveolar bone loss was observed using micro-CT scans. A periodontitis model was considered successfully established when the model group showed significant differences in bone loss (ABL > 0.5 mm) and histological inflammation compared to the healthy control group.
[0152] 1.2 Grouping and Processing
[0153] Twelve 8-week-old clean-grade male SD rats, weighing (280±20) g, were selected. A bilateral maxillary second molar periodontitis model was established in all rats according to the model establishment method described in 1.1 above. The rats were then randomly divided into 4 groups (n=3 per group):
[0154] Group A (PBS control group): PBS treatment was administered.
[0155] Group B (Nano Ag Group): Treatment with nano Ag particle dispersion (100 µg / mL).
[0156] Group C (Nano Fe3O4 Group): Treatment was given with a dispersion of nano Fe3O4 particles (100 µg / mL).
[0157] Group D (Mn / Ag-Fe3O4 group): treated with Mn / Ag-Fe3O4 dispersion (100 µg / mL).
[0158] After the periodontitis model was successfully constructed, the ligature wire was removed. Once a day, 10 µL of the corresponding treatment agent was injected locally into the gingival sulcus of each experimental tooth using a micro-injector for 7 consecutive days.
[0159] After all treatments were completed, all rats were euthanized by overdose anesthesia. The maxilla was completely separated, and the soft tissue attached to the bone surface was removed. The removed maxilla was immersed in 4% paraformaldehyde solution and fixed overnight at 4°C. Subsequent micro-CT scans and decalcified sections were performed for observation.
[0160] 1.3 Micro-CT Analysis and Bone Metrology Evaluation
[0161] A complete maxillary bone sample fixed with 4% paraformaldehyde was placed in a Micro-CT scanner stage, and the scan data was used to reconstruct the three-dimensional structure using evaluation software. Osteometric analysis was performed using 3D analysis software, with the root regions of the first and second maxillary molars as the regions of interest (ROIs). The ROI boundaries were manually delineated in 3D space, ensuring that all periodontal supporting tissues (alveolar bone and periodontal ligament space) were included and excluding hard dental tissues. Within the defined ROI, the following parameters were automatically calculated: alveolar bone loss (ABL), bone volume fraction (BV / TV), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp). All parameters were calculated according to international osteometric standards.
[0162] 1.4 Histopathological observation
[0163] The maxillary decalcified specimens were dehydrated, fixed in paraffin, and sectioned using standard methods. They were then stained with H&E and Masson staining and observed under an optical microscope to observe pathological tissue changes.
[0164] 1.5 Biosafety Assessment
[0165] After the experiment, rats were euthanized, and major organs such as the heart, liver, spleen, lungs, and kidneys were harvested. These organs were rinsed with physiological saline and fixed in 4% paraformaldehyde for 48 h. They were then embedded in paraffin, sectioned to a thickness of 4 µm, and stained with hematoxylin and eosin (HE). The tissue structure of each organ was carefully examined under a light microscope to check for integrity and normal cell morphology. The presence of inflammation, necrosis, or fibrosis was assessed, and a semi-quantitative score was assigned based on the severity.
[0166] 1.6 Statistical Analysis
[0167] All data are expressed as mean ± standard deviation. Statistical analysis was performed using SPSS software. One-way ANOVA was used for comparisons among multiple groups. If a difference was statistically significant, the LSD method (when variances are homogeneous) was used for pairwise comparisons. Independent samples t-tests were used for comparisons between two groups. P < 0.05 indicated a statistically significant difference, and P < 0.01 indicated a highly statistically significant difference.
[0168] 2 Results
[0169] 2.1 Mn / Ag-Fe3O4 nanozymes effectively inhibit the progression of periodontitis and promote periodontal tissue repair.
[0170] Micro-CT analysis confirmed that the Mn / Ag-Fe3O4 nanozyme has a significant in vivo osteogenic effect. Three-dimensional reconstructed images (0A) visually demonstrated that, compared to the significant bone defects in the PBS control group, the bone defect areas in the Mn / Ag-Fe3O4 treatment group were effectively filled with new bone tissue, and the bone contour was largely restored. Its repair effect was superior to that of the nano-Ag group and the nano-Fe3O4 group.
[0171] Quantitative analysis of bone biometric parameters, such as Figure 10 As shown, the alveolar bone loss (ABL) in the Mn / Ag-Fe3O4 group was 0.35±0.07 mm, significantly lower than that in the PBS control group (0.82±0.09 mm, P<0.01), the nano-Ag group (0.65±0.08 mm, P<0.05), and the nano-Fe3O4 group (0.65±0.08 mm, P<0.05). The bone volume fraction and trabecular thickness in the Mn / Ag-Fe3O4 group were significantly higher than those in the control groups, while the trabecular separation was significantly reduced. These results indicate that the local application of Mn / Ag-Fe3O4 can not only effectively inhibit alveolar bone resorption in experimental periodontitis but also actively promote bone recovery and optimized reconstruction of trabecular microstructure. Its osteogenic effect is better than that of single-component nanomaterials.
[0172] 2.2 Mn / Ag-Fe3O4 effectively reduces tissue inflammation
[0173] HE staining results are as follows Figure 11 As shown in Figure A, compared with the PBS control group, the degree of inflammatory cell infiltration in the periodontal tissues of the Mn / Ag-Fe3O4 treatment group was significantly reduced. In the control group, a large number of inflammatory cells were diffusely distributed in the subepithelial and lamina propria connective tissues of the gingiva, while the number of inflammatory cells in the Mn / Ag-Fe3O4 group was significantly reduced, and they were mostly confined to the superficial areas, indicating that this material can effectively inhibit the inflammatory response in periodontal tissues.
[0174] Masson staining results are as follows: Figure 11 As shown in Figure B: Compared with the PBS control group, the Mn / Ag-Fe3O4 treatment group showed a wider area of red mineralized bone tissue at the alveolar bone margin, indicating that it promoted new bone formation and mineralization. Simultaneously, the periodontal ligament region of this group exhibited denser, more orderly arranged blue collagen fibers, suggesting good periodontal soft tissue regeneration. This indicates that this type of enzyme nanomaterial has a synergistic effect on the repair of both periodontal hard and soft tissues.
[0175] 2.3 Biosafety of Mn / Ag-Fe3O4
[0176] After treatment, histopathological examination of the heart, liver, spleen, lungs, and kidneys of the rats was performed, such as... Figure 12As shown in the HE-stained sections, the organ tissue structures of rats in each treatment group (including the Mn / Ag-Fe3O4 group) were intact and clear, with normal cell morphology. No obvious pathological changes such as inflammatory infiltration, edema, degeneration, or necrosis were observed. This indicates that one week of local gingival sulcus administration of Mn / Ag-Fe3O4 did not cause observable systemic toxicity or organ dysfunction in the experimental rats.
[0177] In summary, this invention successfully prepared an iron-manganese composite enzyme-like nanomaterial (Mn / Ag-Fe3O4). Transmission electron microscopy (TEM) showed that its inorganic core particle size was approximately 10 nm with a relatively uniform size distribution. Dynamic light scattering (DLS) measured the hydration kinetic diameter of this enzyme-like nanomaterial in aqueous medium to be approximately 960 nm, indicating that it tends to form nanoparticle aggregates in solution. This enzyme-like nanomaterial exhibits significantly enhanced POD-like activity in acidic environments, efficiently catalyzing the generation of hydroxyl radicals, and also possesses CAT-like activity under neutral conditions. In vitro antibacterial experiments showed that Mn / Ag-Fe3O4 (100 µg / mL) had a broad-spectrum and rapid bactericidal effect against MRSA, E. coli, and P. gingivalis planktonic bacteria and biofilms, reducing viable bacterial count by 4–5 logarithmic orders and achieving a biofilm inhibition rate of 28.2%–52.1%, significantly outperforming single-component nanomaterials. In vivo experiments confirmed that the alveolar bone loss in the Mn / Ag-Fe3O4 treatment group (0.35 mm ± 0.07 mm) was significantly lower than that in the PBS control group (0.82 mm ± 0.09 mm, P < 0.01) and the single-material group. Histopathological examination showed reduced inflammation and good collagen fiber reconstruction. Safety evaluation showed that the cell viability was >85% at a concentration of 100 µg / mL, and no obvious pathological damage was observed in major organs.
[0178] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A type of iron-manganese composite enzyme-like nanomaterial, characterized in that, The enzyme-like nanomaterials are prepared by co-precipitation-hydrothermal method combined with high-temperature calcination using trivalent water-soluble iron salts, divalent water-soluble iron salts, water-soluble manganese salts, and water-soluble transition metal salts in a molar ratio of 1:(0.3~0.7):(0.05~0.3):(0.01~0.1).
2. The iron-manganese composite enzyme-like nanomaterial according to claim 1, characterized in that, The enzyme-like nanomaterial is composed of trivalent water-soluble iron salt, divalent water-soluble iron salt, water-soluble manganese salt, and water-soluble transition metal salt in a molar ratio of 1:(0.4~0.6):(0.1~0.2):(0.02~0.08).
3. The iron-manganese composite enzyme-like nanomaterial according to any one of claims 1 to 2 is characterized in that, The trivalent water-soluble iron salt is any one of ferric chloride, ferric sulfate, ferric nitrate, and their hydrates.
4. The iron-manganese composite enzyme-like nanomaterial according to any one of claims 1 to 2, characterized in that, The divalent water-soluble iron salt is any one of ferrous chloride, ferrous sulfate, ferrous nitrate, and their hydrates.
5. The iron-manganese composite enzyme-like nanomaterial according to any one of claims 1 to 2, characterized in that, The water-soluble manganese salt is any one of manganese chloride, magnesium sulfate, manganese nitrate, and their hydrates.
6. The iron-manganese composite enzyme-like nanomaterial according to any one of claims 1 to 2, characterized in that, The water-soluble transition metal salt is any one of the water-soluble gold, silver, copper, cobalt, nickel, titanium, chromium, molybdenum, palladium, and platinum salts.
7. A method for preparing an iron-manganese composite enzyme-like nanomaterial according to any one of claims 1 to 3, characterized in that, The soluble transition metal salt is prepared according to the following steps: Step 1: Dissolve 1-10g of γ-polyglutamic acid in 25-250mL of deionized water to form a viscous solution. Under nitrogen protection, add divalent and trivalent water-soluble iron salts, along with water-soluble manganese salts and soluble transition metal salts, and stir until homogeneous. Step 2: Under nitrogen protection, add 1.0 mol / L NaOH solution dropwise to adjust the pH to 9.5-10.
0. The solution will turn from yellow to black, and Fe3O4 crystal nuclei will be generated. Continue stirring for 30 min. Step 3: Transfer the suspension to a high-pressure reactor and react at a constant temperature of 200-220℃ for 24-36 hours to carbonize γ-PGA into a biochar substrate; after the reaction is completed, cool to room temperature, filter, and collect solid product 1. Step 4: After washing and drying solid product 1, place it in a tube furnace and calcine it at 500-550℃ under nitrogen protection at a rate of 5-10℃ / min for 3-5 hours. After natural cooling, collect solid product 2. Step 5: Disperse solid product 2 with deionized water, perform magnetic separation using a magnet to remove unreacted impurity ions, and vacuum dry to obtain the iron-manganese composite enzyme-like nanomaterial.
8. The use of the iron-manganese composite enzyme-like nanomaterial as described in any one of claims 1 to 3 in the preparation of drugs for treating periodontitis.